The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/mph.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Blastic Plasmacytoid Dendritic Cell Neoplasm: A Systematic Literature Review

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare aggressive hematologic malignancy characterized by frequent skin involvement that most commonly affects older patients. BPDCN is known to have a poor prognosis. Our objective was to assess if outcome and disease prognosis were independently influenced by age when evaluated with clinical presentation, sex, and treatment regimens. We conducted a systematic review to identify BPDCN cases, to compare pediatric BPDCN cases with adult cases. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 118 publications
2
63
2
Order By: Relevance
“…In 2008, BPDCN was reclassified by WHO as an AML‐related precursor neoplasm, and can be classified by its pattern of cell surface markers . In a recent review of 357 cases, 74 cases were below age 18 years . In the pediatric cohort sex distribution was nearly equal (females 45%), whereas only 26% were females in the adult cohort.…”
Section: Description Of Phenotypic Traits and Genetic Resultsmentioning
confidence: 99%
“…In 2008, BPDCN was reclassified by WHO as an AML‐related precursor neoplasm, and can be classified by its pattern of cell surface markers . In a recent review of 357 cases, 74 cases were below age 18 years . In the pediatric cohort sex distribution was nearly equal (females 45%), whereas only 26% were females in the adult cohort.…”
Section: Description Of Phenotypic Traits and Genetic Resultsmentioning
confidence: 99%
“…A recent literature review evaluating adult's children's responses to first‐line therapy found that older age and hematologic organ involvement at presentation were associated with worse outcomes, acute lymphoblastic leukemia–type chemotherapy was tied to better outcomes, and sex was not predictive of treatment response. Although the presence of cutaneous lesions at diagnosis was not significantly associated with response to first‐line therapy, it was correlated with worse prognosis at 18‐month follow‐up after initial remission …”
Section: Discussionmentioning
confidence: 87%
“…This malignancy typically affects older men (median age 67 years) . It is exceptionally rare in children, with fewer than 75 reported cases in the literature . Clinical manifestations are variable and include single or multiple, nontender, sometimes pruritic, erythematous to violaceous papules, plaques, or nodules .…”
Section: Introductionmentioning
confidence: 99%
“…It is highly responsive to chemotherapy used for ALL, acute myeloid leukemia (AML) and non-Hodgkin lymphoma, but the median event-free survival is only 10 months. 4 Some patients received long-term survival after allo-SCT, especially children, but there were still 30%–40% of them who experienced relapse even after performing allo-SCT. 5 Hence, the understanding of the pathobiology of BPDCN and the development of novel agents is urgently demanded.…”
Section: Discussionmentioning
confidence: 99%